2014
DOI: 10.3892/etm.2014.2080
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in gastric mucosal factors associated with peptic ulcer bleeding

Abstract: A close association has been established between climate and peptic ulcer bleeding (PUB). The incidence of PUB in cold climates is significantly higher than that in hot climates. In this study, gastric mucosal damage and its barrier function (through associated barrier factors) in extreme climate conditions were examined to investigate the pathogenesis of PUB in extreme cold climates. Gastric juice and biopsy specimens were collected from 176 patients with peptic ulcer. Conventional hematoxylin and eosin stain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 18 publications
0
24
0
1
Order By: Relevance
“…Diminished barrier protection, crowding (70), and increased efficiency of respiratory droplet transmission (71) during the winter may contribute to enhanced RTI incidence. An association between compromised mucosal barrier function, due to a reduction in gastric mucosal factors, and the seasonal peak of peptic ulcer disease occurrence in winter has also been reported (156). Moreover, epidemiological studies on rheumatoid arthritis disease activity report that rainy and cold weather appear to increase joint pain and stiffness (1, 48, 95).…”
mentioning
confidence: 95%
“…Diminished barrier protection, crowding (70), and increased efficiency of respiratory droplet transmission (71) during the winter may contribute to enhanced RTI incidence. An association between compromised mucosal barrier function, due to a reduction in gastric mucosal factors, and the seasonal peak of peptic ulcer disease occurrence in winter has also been reported (156). Moreover, epidemiological studies on rheumatoid arthritis disease activity report that rainy and cold weather appear to increase joint pain and stiffness (1, 48, 95).…”
mentioning
confidence: 95%
“…Protection against mucosal injury includes tight intercellular junctions, mucus secretion and mucosal blood flow, cellular restitution, prostaglandin E 2. epithelial renewal. Drugs such as sucralfate, colloidal bismuth and aluminum containing antacids (Yuan et al, 2015).Gastric ulcers have long been rated as one of the most common diseases affecting humans and young people in particular (Saad et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to these findings found in our study, it has recently been suggested that cold climate conditions increase the incidence of bleeding especially due to peptic ulcer. Yuan et al, in their study, observed a decrease in barrier functions of gastric mucosa and an increase at mucosa damage in cold climate conditions, and they claimed that this increased the incidence of peptic ulcer bleeding (9). In many other studies, it has been claimed that the frequency of UGB increases because of the increase in the incidence of helicobacter pylori and NSAID usage in winter (5,7).…”
Section: Discussionmentioning
confidence: 94%